Docetaxel maculopathy. (2016) - Haq, Imran; Salvi, Sachin; Brown, Lawrence; Rennie, Ian; Rundle, Paul
Abstract: A 56 year old retired theatre nurse who has metastatic breast carcinoma complains of reduced vision in the left eye since being started on Docetaxel (Taxotere), an oral anti-mitotic chemotherapeutic agent. Best corrected visual acuity was 6/18 in the left eye, and 6/9-1 in the right. Clinical examination and subsequent examination with optical coherence tomography and Intravenous Fluorescein angiography revealed evidence suggestive of drug related maculopathy. No abnormal findings were present in the right eye. As far as we are aware, this is the first reported case of maculopathy following commencement of Docetaxel with the absence of macular oedema.